Early Dengue Virus Protein Synthesis Induces Extensive Rearrangement of the Endoplasmic Reticulum Independent of the UPR and SREBP-2 Pathway - Peña, José; Harris, Eva (PLOS ONE, 2012)
The rearrangement of intracellular membranes has been long reported to be a common feature in diseased cells. In this study, we used dengue virus (DENV) to study the role of the unfolded protein response (UPR) and sterol-regulatory-element-binding-protein-2 (SREBP-2) pathway in the rearrangement and expansion of the endoplasmic reticulum (ER) early after infection. Using laser scanning confocal and differential interference contrast microscopy, we demonstrate that rearrangement and expansion of the ER occurs early after DENV-2 infection. Through the use of mouse embryonic fibroblast cells deficient in XBP1 and ATF6, we show that ER rearrangement early after DENV infection is independent of the UPR. We then demonstrate that enlargement of the ER is independent of the SREBP-2 activation and upregulation of 3-hydroxy-3-methylglutaryl-Coenzyme-A reductase, the rate-limiting enzyme in the cholesterol biosynthesis pathway. We further show that this ER rearrangement is not inhibited by the treatment of DENV-infected cells with the cholesterol-inhibiting drug lovastatin. Using the transcription inhibitor actinomycin D and the translation elongation inhibitor cycloheximide, we show that de novo viral protein synthesis but not host transcription is necessary for expansion and rearrangement of the ER. Lastly, we demonstrate that viral infection induces the reabsorption of lipid droplets into the ER. Together, these results demonstrate that modulation of intracellular membrane architecture of the cell early after DENV-2 infection is driven by viral protein expression and does not require the induction of the UPR and SREBP-2 pathways. This work paves the way for further study of virally-induced membrane rearrangements and formation of cubic membranes.